2011
DOI: 10.1111/j.1475-2743.2011.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cow manure biochar on maize productivity under sandy soil condition

Abstract: In this study, we performed a greenhouse experiment to investigate the effect of cow manure biochar on maize yield, nutrient uptake and physico‐chemical properties of a dryland sandy soil. Biochar was derived from dry cow manure pyrolysed at 500 °C. Cow manure biochar was mixed with a sandy soil at the rate equivalent to 0, 10, 15 and 20 t biochar per hectare. Maize was used as a test crop. Results of the study indicated that cow manure biochar contains some important plant nutrients which significantly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
383
9
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(441 citation statements)
references
References 38 publications
39
383
9
10
Order By: Relevance
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have reported increased crop yield (Subedi et al, 2016a;Vaccari et al, 2011;Usman et al, 2016;Kammann et al, 2012;Baronti et al, 2010;Uzoma et al, 2011;Houben et al, 2013;Genesio et al, 2015;Cornelissen et al, 2013;De La Rosa et al, 2014;Fox et al, 2014;Gregory et al, 2014;Lin et al, 2015;Schmidt et al, 2015;Butnan et al, 2015;Laghari et al, 2015;Mandal et al, 2016). Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
“…Others have reported no yield effect (Cornelissen et al, 2013;Uzoma et al, 2011;Nelissen et al, 2015;Subedi et al, 2016aSubedi et al, , 2016bNielsen et al, 2014;Tammeorg et al, 2014;Suddick and Six, 2013;Schmidt et al, 2014;Bass et al, 2016). Conversly, few studies have instead described reduced crop yields (Deenik et al, 2010;Baronti et al, 2010;Marks et al, 2014;Nelissen et al, 2014;Bass et al, 2016;Butnan et al, 2015;Laghari et al, 2015).…”
Section: Biochar Effects On Crop Productivitymentioning
confidence: 99%
“…Liu et al [33] reviewed published data from 59 pot experiments and 57 field experiments, concluding that crop productivity was increased by 11 % on average. Uzoma et al [34] reported the effects of biochar produced from cow manure on corn yield, nutrient uptake, and physicochemical properties when used on a sandy soil. They found that applying 15 or 20 t ha −1 of biochar significantly increased corn grain yield by 150 or 88 %, respectively, when compare to an untreated control.…”
Section: Crop Productivitymentioning
confidence: 99%
“…A. A. MOUSA nutrients while simultaneously improving the physical and biological properties of the soil (Woolf et al, 2010 andUzoma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%